MicroRNA Hsa-Let-7b Regulates the Osteogenic Differentiation of Human Periodontal Ligament Stem Cells by Targeting CTHRC1. (14th December 2021) - Fu, Lin; Li, Na; Ye, Yu; Ye, Xiaying; Xiao, Tong; Wu, Xiao; Ma, Yanxia; Yu, Jinhua
Abstract : Let-7 miRNA family has been proved as a key regulator of mesenchymal stem cells' (MSCs') biological features. However, whether let-7b could affect the differentiation or proliferation of periodontal ligament stem cells (PDLSCs) is still unknown. Here, we found that the expression of hsa-let-7b was visibly downregulated after mineralization induction of PDLSCs. After transfected with hsa-let-7b mimics or inhibitor reagent, the proliferation ability of PDLSCs was detected by cell counting kit-8 (CCK-8), flow cytometry, and 5-ethynyl-2-deoxyuridine (EdU) assay. On the other hand, the osteogenic differentiation capacity was detected by alkaline phosphatase (ALP) staining and activity, alizarin red staining, Western blot, and quantitative real-time reverse-transcription polymerase chain reaction (qRT-PCR). We verified that hsa-let-7b did not significantly impact the proliferation ability of PDLSCs, but it could curb the osteogenic differentiation of PDLSCs. Besides, we predicted CTHRC1 acts as the downstream gene of hsa-let-7b to affect this process. Moreover, the combination of CTHRC1 and hsa-let-7b was verified by dual luciferase reporter assay. Our results demonstrated that the osteogenic differentiation of PDLSCs was enhanced after inhibiting hsa-let-7b, while was weakened after cotransfection with Si-CTHRC1. Collectively, hsa-let-7b can repress the osteogenic differentiation of PDLSCs by regulating CTHRC1.